Impact of xenogenic mesenchymal stem cells secretome on a humoral component of the immune system - Moskalov, Vitalii; Koshova, Olena; Ali, Sabina; Filimonova, Nataliia; Tishchenko, Irina (My University, 2023)
Objective. To determine such parameters of humoral immunity as the number of antibody-forming cells and the titer of antibodies in the blood under the action of the whole fraction of the secretome of xenogenic mesenchymal stem cells in mice with a normal immune status and mice with secondary immunodeficiency caused by the hydrocortisone acetate. Methods. The following methods were used in the study: isolation of mesenchymal stem cells from the bone marrow of cattle; culturing of isolated cells and obtaining a conditioned medium containing exometabolites with subsequent purification; modeling of secondary immunodeficiency in mice; setting up a test on mice to determine the number of antibody-forming cells in the spleen and hemagglutinin titers in blood serum; statistical data analysis. Results. A study of the impact of the secretome of xenogenic mesenchymal stem cells (MSCs) on the humoral arm of immunity in mice with a normal immune status showed a significant increase in the antibody-forming cells count compared with the control by 3.4-8.8 times when administered intramuscularly and by 4.2-5.4 times when administered subcutaneously (at the same time, in the group of the reference drug, the increase was four times), as well as an increase in the titer of hemagglutinins concerning the control by 25-95% when administered intramuscularly and 32-52% when administered subcutaneously (the reference drug Thymalin was at the control level). With intramuscular administration, a clear relationship was observed between the concentration of MSC secretome and the biological effect (high significant positive correlation: ρ = 0.99, p ≤ 0.05 for calculating AFC; ρ = 0.97, p ≤ 0.05 for HA titer). Lethality in the group of animals what administered only hydrocortisone acetate (HCA, positive control) was 100%. The use of the mesenchymal stem cells secretome increased the survival of animals by 50% by stimulating the formation of the required number of antibody-forming cells and antibody titer, except for the subcutaneous route of administration (at the level of immunized control, animals with a normal immune status). The reference drug showed a result at a level significantly lower than the immunized control. The antibody titer with the subcutaneous route of administration of secretion of MSCs was significantly lower than the immunized control but significantly higher concerning the reference drug. Conclusion. The administration of the secretome of xenogenic mesenchymal stem cells stimulated the humoral arm of immunity as same in mice with normal immune status as in mice with secondary immunodeficiency. The data obtained supplement the information on the introduction of live mesenchymal stem cells. Live allogeneic MSCs have a suppressive effect on B cells, while xenogenic MSCs cause a response on themselves. The secretome of xenogenic MSCs does not contain surface immunogenic molecules that are carried by living cells, but nevertheless increases the activity of the humoral component of immunity. The mechanisms of this effect require further study
Impact of xenogenic mesenchymal stem cells secretome on a humoral component of the immune system / Vitalii Moskalov, Olena Koshova, Sabina Ali, Nataliia Filimonova // WikiJournal of Medicine. – 2023. – 10(1):1
Keywords: humoral immunity,immunodeficiency